2001
DOI: 10.1021/cm001188o
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature and Pressure on the Densification, Microstructure, and Electrical Properties of the Dual-Phase System Y2O3-Doped ZrO2 and RuO2

Abstract: Dual-phase nanocomposite powders of 3Y-TZP (tetragonal-ZrO 2 doped with 3 mol % Y 2 O 3 ) and RuO 2 have been prepared and densified into compacts. The electrical conductivity of the densified compacts was correlated with the microstructure. Variations in the synthesis method and powder composition influenced the densification and resulting microstructure of the composites. Densification of the composites was sensitive to changes in experimental temperature/pressure conditions. Sinterforging the material in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Full densification (>98%) of this compact can readily be achieved under pressureless sintering (1450 °C) or sinterforging (1150 °C, 50 MPa) conditions, as we previously demonstrated [9]. In those cases, however, irreversible inhomogeneous microstructural changes were evident, caused by evaporation and condensation sequences of gaseous RuO 4 (formed from aerial oxidation of RuO 2 ) whereby the initial nano-sized powder grains were destroyed through rigorous aggregation and eventually replaced by growth of numerous micro-sized (1-5 µm) grains.…”
Section: Electrical Propertiesmentioning
confidence: 54%
See 1 more Smart Citation
“…Full densification (>98%) of this compact can readily be achieved under pressureless sintering (1450 °C) or sinterforging (1150 °C, 50 MPa) conditions, as we previously demonstrated [9]. In those cases, however, irreversible inhomogeneous microstructural changes were evident, caused by evaporation and condensation sequences of gaseous RuO 4 (formed from aerial oxidation of RuO 2 ) whereby the initial nano-sized powder grains were destroyed through rigorous aggregation and eventually replaced by growth of numerous micro-sized (1-5 µm) grains.…”
Section: Electrical Propertiesmentioning
confidence: 54%
“…In those cases, however, irreversible inhomogeneous microstructural changes were evident, caused by evaporation and condensation sequences of gaseous RuO 4 (formed from aerial oxidation of RuO 2 ) whereby the initial nano-sized powder grains were destroyed through rigorous aggregation and eventually replaced by growth of numerous micro-sized (1-5 µm) grains. A sideeffect of this micro-sized grain microstructure was that it allowed for good electronic percolation pathways and showed metallic-like conduction, namely σ = 4.4 × 10 3 and 2.1 × 10 3 S cm -1 at 15 mol% [9] and 10 mol% RuO 2 [this work], respectively. These results are summarized in Table 1.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…This might be caused by the second phase of RuO 2 because of its high conductivity (1:4 Â 10 6 Sm À1 at 293 K). Raming et al 15) reported that YSZ (Y 2 O 3 -stabilized ZrO 2 )-RuO 2 composite had high electrical conductivity due to agglomerated RuO 2 . However, the second phase of CaO in CRO at R Ru/Ca < 1:0 may result in the decrease in because CaO is an insulating material (<10 À8 Sm À1 at 293 K).…”
Section: Resultsmentioning
confidence: 99%
“…It places restrictions on their possible applications. Raming et al 22 prepared dual-phase nanocomposite powders of tetragonal-ZrO 2 doped with 3 mol% Y 2 O 3 and RuO 2 and densified them into compacts by hot-pressing. However, the sinterforging or hot-pressing method is an expensive sintering method and is not always available in the laboratory.…”
Section: Introductionmentioning
confidence: 99%